Mechanisms in disputeroutine procedure minero - Escajadillo Chimayco, Francisco (2016)
The development of the present work has the purpose of realize an analysis, from a systematic and functional perspective, of the administrative resources and the special procedures in the frame of the ordinary mining procedure, the same ones that have for object question the present or future administrative decisions. For it, we believed convenient to grant the generic name of «Mechanisms of challenging» in order not to change his own nature. In this sense, the mechanisms of challenging – in conformity with to what we have been determined – understood as means that allow to carry out the contradictory pretensions of the administered ones or particulars with regard to an administrative determined or determinable action, fulfill the same function and chase the same purpose: The control of legality in the administrative way of an administrative concrete or future decision in certain sense, allowing with it, to guarantee the right to a due procedure of which the administered ones and parti